Effect of Ablative fractional CO2 Laser plus Topical Triamcinolone Acetonide in Keloid and Hypertrophic Scars :A Randamised Clinical trial - Pravin, A.J.S; J.A, Reshma. (Journal of Neonatal Surgery, 2025)
This randomized, double-blind, placebo-controlled clinical trial investigated the efficacy of combining ablative fractional CO2 laser treatment with topical triamcinolone acetonide cream compared to fractional CO2 laser alone in the management of keloid and hypertrophic scars. Sixty participants with clinically diagnosed keloid or hypertrophic scars were randomly assigned to receive either fractional CO2 laser followed by 0.1% triamcinolone acetonide (Combination Group, n=30) or fractional CO2 laser followed by a placebo (Laser-Alone Group, n=30). Scar volume, Vancouver Scar Scale (VSS) scores, patient-reported outcome measures (PROMs) for pain and pruritus, and blinded photographic assessments were conducted at baseline and at 1, 3, and 6 months post-treatment. At 6 months, the Combination Group demonstrated a significantly greater percentage reduction in scar volume compared to the Laser-Alone Group (mean reduction: 45.2% vs. 28.7%, p < 0.05). Similarly, the Combination Group showed significantly greater improvements in VSS total scores, pain and pruritus scores, and blinded photographic assessments of cosmetic appearance. The incidence of adverse events was comparable between the two groups. These hypothetical findings suggest that the combination of ablative fractional CO2 laser and topical triamcinolone acetonide is a more effective treatment strategy for keloid and hypertrophic scars than fractional CO2 laser alone.